Music in the Moment - Levinson, Jerrold (Ithaca, NY Cornell University Press, 1997)
What is required for a listener to understand a piece of music? Does aural understanding depend upon reflective awareness of musical architecture or large-scale musical structure? Jerrold Levinson thinks not. In contrast to what is commonly assumed, Levinson argues that basic understanding of music only requires properly grounded, present-focused attention, and that virtually everything in the comprehension of extended pieces of music that suggests explicit architectonic awareness can be explained without positing a conscious grasp of relationships across broad spans.
Keywords: Music philosophy and esthetics